'Heritage' and 'cultural practice' in a globalized disaster: a preliminary thematic analysis of documents produced during the Ebola epidemic of 2013–2015. Issue 5 (29th July 2018) - O'Kane, David; Boswell, Rosabelle
ABSTRACT: The Ebola crisis of 2013–2015 highlighted the relationship between cultural heritage, neoliberal globalization and public health. It also raised the problem of cultural compatibility between organizations within the global 'epidemic space', which intruded on the pre-existing 'heritage space'. In this paper, we discuss the differences and disjunctures between 'heritage' as it was explicitly and implicitly defined by two organizations positioned very differently in the global epidemic space – UNESCO, and the University of Makeni, Sierra Leone's first private university. A thematic analysis of documents produced by these institutions reveals that they both placed the themes of human dignity and cultural heritage at the forefront of their responses. It also reveals that they dealt with those themes in sharply disjunctive ways, indicating the limits of cultural compatibility within the global 'epidemic space'.